Peran Serta Stakeholder Dalam Membentuk City Branding The Spirit Of Java di Jalan Slamet Riyadi Surakarta - Mustika, Herdyanah (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Koridor Slamet Riyadi street becomes the main area for develop city branding the spirit of java. Its presence as the main gateway into the city to lead directly to the center of the city of Surakarta increasingly strengthened characterized as Java. The aim of this study is identify the characteristics that form and find out the role of the stakeholders that involved in develop Solo the spirit of java in the corridor Slamet Riyadi street. The result showed that the characteristics of the spirit of java formed Slamet Riyadi street consists of eight physical characteristics and four non-physical characteristics. Then from characteristics analysis are use meassure the role of stakeholders, the result is that the government in the physical characteristics indicate the role of full control, the government in non-physical characteristics indicate the role of shared control. Private sector in a physical characteristics indicate a role in the consultative and non-physical characteristics indicate the role of shared control. Then citizen in the physical characteristics indicate the role of none, while in the non-physical characteristics have a role shared control.